Evaluation using Multi-criteria Analysis of Forest and Land Rehabilitation Program in Butuh Kidul Village, Kalikajar Sub District, Wonosobo Regency, Central Java - Aris Jatmiko; Ronggo Sadono; Lies Rahayu Wijayanti Faida (Jurnal Ilmu Kehutanan)
Forest and land rehabilitation program aims to restore, maintain, and improve forest and land function. The ultimate goal of this program is sustainability of forest-land capacity and productivity as supporting life system. Evaluation to this program is a necessity in determining the success of land and forest rehabilitation, reducing the risks and increasing the potential success. This research was carried out to set up the criteria and indicators and to test them against the performance of forest and land rehabilitation in Butuh Kidul Village, Kalikajar Sub District, Wonosobo District, Central Java. Multicriteria analysis using Analytical Hierarchy Process (AHP) was adopted in this study. Evaluation process was began by formulating a set of criteria and indicators, followed by exercising judgment and scoring by experts, people, and other stakeholders under AHP framework. The results showed that there were four key criteria to evaluate the success of Forest and Land Rehabilitation, namely: (i) prerequisite, (ii) production, (iii) ecology, and (iv) socio-economic criteria. From experts judgment comparison, the weighed preferences were, respectively : 0,05; 0,21; 0,43; and 0,31. Based on these figures, the comparative value of Forest and Land Rehabilitation in Butuh Kidul Village, Kalikajar Sub District, Wonosobo District, Central Java was 0,80 in the range of 0,33-1. The percentage of success rate was 70,55 %, or the “moderate”, indicating that RHL in this case may still be enhanced.